ELEPHANT TUSKS AND BELIS TRADITION BY LAMAHOLOT COMMUNITY IN EAST NUSA TENGGARA, INDONESIA - Sukmantoro, Wishnu; Suyitno, Agus (Jurnal Nusa Sylva, 2023)
The unique dowry tradition in Indonesia is called “belis” with the raw elephant tusks where the origin is still a mystery and will certainly be controversial at this time because they are prohibited to be traded and used. The study was conducted in May-June 2022 in East Flores, Adonara and Lembata of East Nusa Tenggara province through semi-systematically interview method. It aimed at examining the belis and use of elephant tusks in belis tradition of Lamaholot community. Based on interviews to 101 respondents of key person including traditional leaders, the elephant tusks and the belis tradition have existed for hundred years ago and as a symbol as the glory of women and their high dignity. There were in the belis tradition three-furnace system which served as central point, coda form and dowry negotiation between male and female families. The local community still wanted to preserve the tradition, but it was desire to avoid the use of the ivory to reduce tradition cost. Until today, the Lamaholot community is in a dilemma of preserving the long living tradition of the ivory belis in which it is increasingly rare and the elephant conservation in Indonesia is getting more important.